2021
DOI: 10.3389/fphar.2021.752825
|View full text |Cite
|
Sign up to set email alerts
|

The Disulfiram/Copper Complex Induces Autophagic Cell Death in Colorectal Cancer by Targeting ULK1

Abstract: Colorectal cancer (CRC) is highly prevalent worldwide, but there has been limited development of efficient and affordable treatment. Induced autophagy has recently been recognized as a novel therapeutic strategy in cancer treatment, and disulfiram (DSF), a well-known antialcohol drug, is also found to inhibit tumor growth in various malignancies. Recently, DSF has been reported to induce excessive autophagy in oral squamous cells; however, little is known about whether it can induce autophagy and suppress prol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…Cuproptosis is a pattern of cell death newly defined by GOLUB et al (Tsvetkov et al, 2022), and its mechanism is distinct from other mechanisms known to regulate cell death. Some previous studies had demonstrated that unbalanced copper homeostasis could induce cell death and exert anti-tumor effects (Jiang et al, 2022), for instance, disulfiram/copper complexes can induce apoptosis in non-small cell lung cancer cells (Wu et al, 2018), induce autophagic death in colorectal cancer cells (Hu et al, 2021) and induce ROS-dependent apoptosis in malignant prostate cells (Safi et al, 2014). However, the current research on cuproptosis is still in its infancy.…”
Section: Discussionmentioning
confidence: 99%
“…Cuproptosis is a pattern of cell death newly defined by GOLUB et al (Tsvetkov et al, 2022), and its mechanism is distinct from other mechanisms known to regulate cell death. Some previous studies had demonstrated that unbalanced copper homeostasis could induce cell death and exert anti-tumor effects (Jiang et al, 2022), for instance, disulfiram/copper complexes can induce apoptosis in non-small cell lung cancer cells (Wu et al, 2018), induce autophagic death in colorectal cancer cells (Hu et al, 2021) and induce ROS-dependent apoptosis in malignant prostate cells (Safi et al, 2014). However, the current research on cuproptosis is still in its infancy.…”
Section: Discussionmentioning
confidence: 99%
“…Hu et al reported that DSF combined with Cu could significantly inhibit the viability of CRC cells and trigger autophagic cell death instead of apoptosis via enhancing the ULK1 level. 221 …”
Section: Crucial Signaling Pathways Of Rcd Subroutines In Cancermentioning
confidence: 99%
“…Hu et al reported that DSF combined with Cu could significantly inhibit the viability of CRC cells and trigger autophagic cell death instead of apoptosis via enhancing the ULK1 level. 221 Targeting PI3KC1/Akt/mTORC1. PI3KC1/Akt/mTORC1 signaling pathway has been considered as the pivotal regulator in various cell processes.…”
Section: Autophagy-dependent Cell Death Signaling Pathways In Cancermentioning
confidence: 99%
“…Recently, there is a study has shown that ULK1 is the most frequently mutated gene in The Cancer Genome Atlas (TCGA)-colorectal adenocarcinoma dataset, implying that ULK1 and its regulatory network may be closely related to colorectal carcinogenesis ( 14 ). Notably, the upregulation of ULK1 significantly induces autophagy-dependent cell death in RKO human CRC cells, which exerts excellent antiproliferative potency ( 15 ).…”
Section: Crucial Pathways For Autophagy Regulation In Crcmentioning
confidence: 99%